2009
DOI: 10.1515/znc-2009-5-606
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Gentiana lutea L. Extracts

Abstract: Methanolic extracts of fl owers and leaves of Gentiana lutea L., together with the isolated compounds mangiferin, isogentisin and gentiopicrin, were used to investigate the antimicrobial activity of the plant. A variety of Gram-positive and Gram-negative bacteria as well as the yeast Candida albicans has been included in this study. Both extracts and isolated compounds showed antimicrobial activity with MIC values ranging from 0.12 -0.31 mg/ml. Our study indicated that the synergistic activity of the pure comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 4 publications
(5 reference statements)
2
31
0
Order By: Relevance
“…1), a natural bioactive xanthone C-glycoside originated from Mangifera indica L. (Anacardiaceae) (Aritomi and Kawasaki, 1969), possesses a wide spectrum of pharmacological activities, including antioxidant (Das et al, 2012), antiinflammatory (Das et al, 2012), antidiabetic (Sellamuthu et al, 2009), anticancer (Shoji et al, 2011), antibacterial (Savikin et al, 2009), anti-human immunodeficiency virus , and radioprotective (Jagetia and Baliga, 2005) actions. Owing to its remarkable bioactivities, mangiferin has attracted increasing attention as a potential candidate.…”
Section: Introductionmentioning
confidence: 99%
“…1), a natural bioactive xanthone C-glycoside originated from Mangifera indica L. (Anacardiaceae) (Aritomi and Kawasaki, 1969), possesses a wide spectrum of pharmacological activities, including antioxidant (Das et al, 2012), antiinflammatory (Das et al, 2012), antidiabetic (Sellamuthu et al, 2009), anticancer (Shoji et al, 2011), antibacterial (Savikin et al, 2009), anti-human immunodeficiency virus , and radioprotective (Jagetia and Baliga, 2005) actions. Owing to its remarkable bioactivities, mangiferin has attracted increasing attention as a potential candidate.…”
Section: Introductionmentioning
confidence: 99%
“…30 Its Methanol extract of flowers and leaves, as well as separated mangiferin, isogentisin, and gentiopicrin show antimicrobial activity against Gram-positive and -negative bacteria as well as the yeast Candida albicans. 31 In one study, the topical application of Teucrium polium L extract accelerated healing of burn wounds. 32 Inhibition of carrageenan-induced inflammation in an animal study showed the anti-inflammatory effect of this plant.…”
Section: Discussionmentioning
confidence: 99%
“…The study also reported that mangiferin did not affect locomotion or motivation. Savikin and co-workers investigated the antimicrobial activity of mangiferin, isogentisin and gentiopicrin, isolated from methanolic extracts of flowers and leaves of Gentiana lutea L., on various gram-positive and gram-negative bacteria as well as the yeast Candida albicans with MIC values ranging from 0.12-0.31 mg/ml [120]. Yoshikawa and group have evaluated the lipolytic effects exhibited by mangiferin at 100 mg/L (P < 0.01) and concluded that it may be involved in the antiobesity effects of Salacia reticulata in rats by inhibition of fat metabolizing enzymes (pancreatic lipase, lipoprotein lipase and glycerophosphate dehydrogenase) and enhanced lipolysis [121].…”
Section: Miscellaneous Activitiesmentioning
confidence: 99%